Role of the landscape in spatial and rural development - Kerékgyártó, Gábor (Acta Agraria Debreceniensis, 2012)
The study is going to reveal the role of landscape potential in spatial and rural development based on the analyses of scientific literature. The target area of the research is three micro regions in Hajdú-Bihar county. In addition to the analyses of scientific literature the study pays attention to the assay of local development concepts and programmes. The conclusion of the study is that the analyses of landscape changes on micro regional level are obstructed by the lack of micro regional spatial development and substantive landscape plans.